Exposure to Leather Tanning Factories Lowers Semen Quality in Mongolian Men (Central Asian Journal of Medical Sciences, 2017)
Objectives: To examine the difference in semen qualities of male workers in leather tanning factories and of those in other industries. Methods: Eighty reproductive aged male workers from six leather tanning factories and eighty-five from non-tanning workplaces participated in the study as the exposed subjects and non-exposed subjects, respectively. Each subject was given a physical examination, required to complete a questionnaire, and asked to supply a semen specimen. Semen analysis on fresh specimens followed the latest World Health Organization guideline. Semen parameters were compared between the exposed and non-exposed subjects using tabulation and chi-square test for categorical variables and t-test or rank-sum test for continuous variables. Multiple linear or logistic regression models were constructed to examine the independent effects of exposure. Results: After adjusting for confounding variables, exposed subjects had significantly higher percentages of grade C motility (p=0.008), mid-piece defect (p=0.009), and tail-defect (p=0.029) in their spermatozoa compared to non-exposed subjects. Liquefaction time was also longer (p=0.046). Conclusion: Leather tanning workers have significantly higher percentages of grade C motility, mid-piece defect, and tail-defect in their spermatozoa.